Effectof sisal fiber(Agavesisalana)andsurfacetreatmenton transverse strength in acrylic resin denture base repair - Maharani, Adella Syvia; Kusuma, Heriyanti Amalia; Wahyuningtyas, Endang (Indonesia Prosthodontic Association, 2021)
Acrylic resin as a denture base material has a disadvantage;it is easily fractured.However, fractures can be re-paired.This study aimed to reveal the effects of sisal fiber (Agave sisalana) and surface treatment onthetrans-versestrengthinacrylicresindenturebaserepair.Alaboratoryexperimentwasconductedon30acrylic resin sam-ples with a size of 65x10x2.5 mm,consisting of group I(was on the repaired section),groupII(sisalwereto the repaired section) and group III (repaired were sisal fibers and applied with monomer). Transverse strength was measuredusinga universal testing machine.The data obtained were analyzed using1-wayANOVA.Theresults showedthat the lowest transverse strengthwas foundin group I(88.30Â±7.38MPa)andthehighest strength was in groupIII (133.45Â±8.38MPa).Based on the results of this study, it can be concluded that the use of sisal fiber and surface treatment can increase the transverse strength in acrylic resin denture base repair.